2019
DOI: 10.1038/s41467-019-12993-x
|View full text |Cite
|
Sign up to set email alerts
|

Quasi Pd1Ni single-atom surface alloy catalyst enables hydrogenation of nitriles to secondary amines

Abstract: Hydrogenation of nitriles represents as an atom-economic route to synthesize amines, crucial building blocks in fine chemicals. However, high redox potentials of nitriles render this approach to produce a mixture of amines, imines and low-value hydrogenolysis byproducts in general. Here we show that quasi atomic-dispersion of Pd within the outermost layer of Ni nanoparticles to form a Pd1Ni single-atom surface alloy structure maximizes the Pd utilization and breaks the strong metal-selectivity relations in ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 69 publications
3
113
0
Order By: Relevance
“…[ 226‐228 ] Tremendous efforts have been devoted to developing the methods of precise synthesis and to understanding the structure‐activity relations in a number of catalytic reactions. [ 226‐233 ] A thorough study of the particle size effect as well as taking the counterparts of ultrafine clusters and single atoms into account is highly necessary, which could provide a much deeper insight of structure‐activity relations and facilitate rational design of advanced metal catalysts. However, such studies in the real catalyst systems have been rarely reported.…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%
“…[ 226‐228 ] Tremendous efforts have been devoted to developing the methods of precise synthesis and to understanding the structure‐activity relations in a number of catalytic reactions. [ 226‐233 ] A thorough study of the particle size effect as well as taking the counterparts of ultrafine clusters and single atoms into account is highly necessary, which could provide a much deeper insight of structure‐activity relations and facilitate rational design of advanced metal catalysts. However, such studies in the real catalyst systems have been rarely reported.…”
Section: Particle Size Effect In Metal Catalysismentioning
confidence: 99%
“…[25][26][27] Currently, the difficulty in controlling the favorable interactions and synergistic effects in SAAs has limited their applications in electrocatalysis. [28][29][30][31][32][33][34] Intermetallics possess long-range atomic ordering and isolated metallic atoms on the surface, which could serve as a promising matrix to construct SAAs, yet that has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of strong metal-support interactions has long been recognized 5 . Of special interest is the stabilization of single-metal atoms on a support, which is rapidly becoming a new frontier in materials chemistry and catalysis [6][7][8][9][10][11] . The single-atom nature of the catalysts can overcome the scarcity of particular elements, such as precious group metals, ubiquitous in catalysis 1,8,12 .…”
Section: Introductionmentioning
confidence: 99%